THE MODEL OF QUANTUM MECHANICS WITH RANDOM NUMBER OF ACTION QUANTA - Рувінський, Марк Аунович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
On the basis of idea about existance of the fundamental quantum of action h / 2 and availability of the stochastic number of action quanta of particle (or system of particles) with the non-uniform Poisson distribution, after the averaging and introduction of the postulate about proportionality of the probability of the zero value of the number of action quanta to the probability density of particle’s position, it may come to the Schrodinger equation and the uncertainty Heisenberg’s relation. The identity principle of the same microparticles is considered and the variational principle of quantum mechanics is formulated from the new point of view.